?COPPER (I) COMPLEXES OF TRIPHENYLPHOSPHINE AND AMINOPHENOL - SULTANA, NAJMA; ARAYNE, M. SAEED; TABASSUM, HAMIDA (Biological Sciences - PJSIR, 1995)
Some new complexes of copper(l) containing mixed ligands having general formula [CuX(PPh,)(Amph)), [Cu1X1(PPh)3(Amph) and [CunZn(PPh3)1(Amph)] [where X =CI', Br, I' and Z = NO,-or SCN', n = 1,4 or'5 and PPh, = triphenylphosphine and Am ph = aminophenol] have been synthesized from [CuX(PPh3)]4 and [CuX (PPh,)z]z in benzene in variable ratios and characterized on the basis of infra red studies and elemental analysis. Magnetic susceptibility and conductivity measurements have also been carried out. These appear to be dimers and polymeric structures having bridging of halides, nitrate or thiocyanate groups between the two copper atoms.